Pengaruh ZPT Alami dan Lama Perendaman terhadap Viabilitas dan Vigor Benih Bawang Merah (True Shallot Seed): The Effect of Natural ZPT and Soaking Time on Seed Viability and Vigor Red Onion (True Shallot Seed) - Zubaidah, Siti; Pandiangan, Meldriany; Oemar, Oesin; Sinaga, Soaloon; Panupesi, Hadinnupan (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2024)
The purpose of this study was to determine and study the real effect of natural growth regulators (ZPT), soaking time and interactions on the viability and vigor of shallot seeds (True Shallot Seed). This research was conducted in April-June 2023 using a factorial Completely Randomized Design (CRD). The first factor was the administration of growth regulators (ZPT) with 4 levels of treatment, namely mineral water, coconut water extract, bean sprout extract and shallot extract. The second factor is immersion time with 3 levels, namely 1, 2 and 3 hours. Variables observed included sprout growth, uniformity of growth, vigor index, germination rate, normal sprout dry weight and sprout length. The results of the study showed that there was a significant effect on the interaction of natural ZPT administration and soaking time on the observed variables of growth uniformity and normal sprout dry weight. It also had a significant effect on the administration of natural ZPT on the variables of sprouting power, growth uniformity, vigor index, germination rate, sprout dry weight. normal and long sprouts, with the best treatment soaking in mineral water. The treatment had no significant effect on the long immersion treatment. Keyword : Natural growth regulator, Soaking time, True seed shallot, Viability, Vigor